2020
DOI: 10.1161/hypertensionaha.120.15558
|View full text |Cite
|
Sign up to set email alerts
|

Ca 2+ -Dependent NOX5 (NADPH Oxidase 5) Exaggerates Cardiac Hypertrophy Through Reactive Oxygen Species Production

Abstract: NOX5 (NADPH oxidase 5) is a homolog of the gp91 phox subunit of the phagocyte NOX, which generates reactive oxygen species. NOX5 is involved in sperm motility and vascular contraction and has been implicated in diabetic nephropathy, atherosclerosis, and stroke. The function of NOX5 in the cardiac hypertrophy is unknown. Because NOX5 is a Ca 2+ -sensitive, procontractile NOX isoform, we questioned whether it plays a role in cardiac hypertrophy. Studies were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 50 publications
1
32
0
Order By: Relevance
“…Widespread disturbance of cellular redox balance throughout the circulatory system is recognized as a general feature of arterial hypertension, whether of primary or secondary etiology. In experimental models of hypertension or other forms of pressure overload, LVH is accompanied by many biochemical, metabolic and signaling disturbances that have been associated with cardiomyocyte hypertrophy, altered myofibrillar contractility, interstitial fibrosis and gradual progression to Calcium/calmodulin-dependent NOX5 may also be implicated [283]. The extent to which these various pathways of ROS production are co-regulated or exhibit cross-talk is unclear.…”
Section: Hypertension/lvh and Redox Signaling In Myocardial Infarctionmentioning
confidence: 99%
“…Widespread disturbance of cellular redox balance throughout the circulatory system is recognized as a general feature of arterial hypertension, whether of primary or secondary etiology. In experimental models of hypertension or other forms of pressure overload, LVH is accompanied by many biochemical, metabolic and signaling disturbances that have been associated with cardiomyocyte hypertrophy, altered myofibrillar contractility, interstitial fibrosis and gradual progression to Calcium/calmodulin-dependent NOX5 may also be implicated [283]. The extent to which these various pathways of ROS production are co-regulated or exhibit cross-talk is unclear.…”
Section: Hypertension/lvh and Redox Signaling In Myocardial Infarctionmentioning
confidence: 99%
“…The nicotinamide adenine dinucleotide phosphate (NADPH) oxidase complex is an important source of ROS in the heart ( Touyz et al, 2020 ). Increased NADPH oxidase activity and expression has been associated with LV hypertrophy in pressure overload models ( Li et al, 2002 ; Zhao et al, 2020 ). The main cellular defenses against increased ROS include enzymes such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) ( D’Oria et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, NOX5-dependent ROS increased the systolic blood pressure levels in a podocyte-specific NOX5 expression knock-in mouse model [ 35 ] or participated in diabetic nephropathy progression [ 36 ]. Moreover, NOX5 is known to potentiate cardiac remodeling and the dysfunction of hypertensive angiotensin II-induced mice expressing NOX5 in the heart under the α-myosin heavy-chain promoter [ 37 ]. Additionally, in another knock-in mouse, which expressed NOX5 under the Tie2 promoter specific to the endothelium and white blood cells, the authors found that chronic NOX5 expression induced elevated systolic blood pressure levels in aging mice [ 38 ].…”
Section: Discussionmentioning
confidence: 99%